To haft and to hold: Evidence for the hafting of Clovis fluted points - Alan Michael Slade (Journal of Lithic Studies, 2021)
Clovis fluted points vary considerably in technology and morphology, but also share a set of attributes, the most diagnostic of which are the flute scars, the remnants of the flake removals from the basal region that travelled up towards the tip. Fluting on Clovis and Clovis-like points generally extends no further than a third of the way up the face of the point. Finished points are usually ground smooth along the base and lower edges, suggesting facilitation of the hafting (attachment) to a wooden shaft or handle by way of an ivory or bone socket. The points may have been hafted directly to a main-shaft and used as a thrusting spear during close encounter attacks, or in the hand as knife or butchery tool. Alternatively, an intermediary shaft, or foreshaft may have been used to secure the point. The suggestion of foreshafts being used by Clovis hunters received support after the discovery of bone rods in association with mammoth remains and Clovis points at the type site at Blackwater Draw, New Mexico in 1936. Several other Clovis-aged sites across North America have yielded ivory and beveled rods that have also been associated with foreshafts and the hafting of Clovis points. Scratches that are present on a couple of Clovis points made on varieties of obsidian, have been identified as being “hafting abrasion” evidence, this roughening of the surface would have helped in securing the point into the shaft or socket. In one example from the Hoyt site in Oregon, remains of a “pitch” or hafting adhesive was discovered in the abrasions in the fluted area of the point.